An Economic Evaluation of the Garrett Lee Smith Memorial Suicide Prevention Program. Issue 1 (16th December 2016) - Godoy Garraza, Lucas; Peart Boyce, Simone; Walrath, Christine; Goldston, David B.; McKeon, Richard
Abstract : For more than a decade, the Garrett Lee Smith Youth Suicide Prevention Program has provided funding for community‐based suicide prevention programs to states, tribes, and colleges across the United States. Recent studies provided evidence of the program's effectiveness in reducing suicide mortality and suicide attempts among youth. This study compares the cost of implementing the program with the estimated savings resulting from avoided hospitalization and emergency department visits associated with the averted suicide attempts. The findings suggest that the cost of implementing multifaceted community‐based suicide prevention strategies may be more than outweighed by savings in the health sector.